The Bugis Chronicle of Bone - Macknight, Campbell; Paeni, Mukhlis; Hadrawi, Muhlis (ANU Press, 2020)
"The Bugis Chronicle of Bone is a masterwork in the historiographical tradition of South Sulawesi in Indonesia. Written in the late seventeenth century for a very specific political purpose, it describes the steady growth of the kingdom of Bone from the fourteenth century onwards. The local conquests of the fifteenth century, closely linked to agricultural expansion, give way to the long conflict with the Makasar state of Gowa in the sixteenth century. Forced Islamisation in 1611 is dealt with in detail, leading finally to first contact with the Dutch East India Company in 1667. This edition presents a diplomatic version of the best Bugis text, together with the first full English translation and an extensive introduction covering the philological approach to the edition, as well as the historical and cultural significance of the work. A structure based on the reigns of successive rulers allows for stories about the circumstances of each ruler and, particularly, the often dramatic processes and politics of succession. The chronicle is a rich source for historians and anthropologists seeking to understand societies beyond Europe. It provides a window on to this Austronesian-speaking society before the impact of significant external influences. This is history from within, covering more than three centuries. "